The politics of defining and alleviating poverty: State strategies and their impacts in rural Kerala - Glyn Williams, Binitha V. Thampi, D. Narayana, Sailaja Nandigama and Dwaipayan Bhattacharyya (Geoforum, 2012)
This paper presents a relational approach to the study of poverty (Mosse, 2010), and uses this to critically evaluate state strategies for identifying and alleviating poverty in Kerala, India. It traces these from national planning documents through to their point of implementation, drawing on qualitative research in two of Kerala’s poorest Districts. Ideas of participatory poverty classification, economic self-reliance and political empowerment are laudable national policy goals, and Kerala has shown innovation in its adaptation of these within the State’s devolved structures of local governance. However, both the framing of policy and its implementation reproduce ideas of individual transitions out of poverty which indicate that the state pays insufficient attention to the highly unequal social and economic relationships repro- ducing poverty in contemporary Kerala – in short, to poverty’s inherently political nature.